Augmentation of NAD+ by Dunnione Ameliorates Imiquimod-Induced Psoriasis-Like Dermatitis in Mice - Lee SH; Kim HJ; Oh GS; Lee SB; Khadka D; Cao W; Choe SK; Shim H; Kim CD; Kwak TH; So HS (Journal of Inflammation Research, 2022)
Seung Hoon Lee,1,* Hyung-Jin Kim,1,* Gi-Su Oh,1 Su-Bin Lee,1 Dipendra Khadka,1 Wal Cao,1 Seong-Kyu Choe,1 Hyeok Shim,2 Chang-Deok Kim,3 Tae Hwan Kwak,4 Hong-Seob So1,4 1Department of Microbiology, Wonkwang University School of Medicine, Iksan, Jeonbuk, 54538, Republic of Korea; 2Department of Hemato-Oncology, Wonkwang University School of Medicine, Iksan, Jeonbuk, 54538, Republic of Korea; 3Department of Dermatology, College of Medicine, Chungnam National University, Daejeon, 34134, Republic of Korea; 4R&D Center, NADIANBIO Ltd, Iksan, Jeonbuk, 54538, Republic of Korea*These authors contributed equally to this workCorrespondence: Hong-Seob So, Department of Microbiology, Wonkwang University School of Medicine, 460 Iksan-Daero, Iksan, Jeonbuk, 54538, Republic of Korea, Tel +82-63-850-6950, Fax +82-63-855-6777, Email jeanso@wku.ac.krBackground: Dunnione has anti-inflammatory properties arising from its ability to alter the ratio of NAD+/NADH through NAD(P)H quinone oxidoreductase 1 (NQO1) enzymatic action, followed by subsequent inhibition of NF-κB and inflammatory cytokines. Psoriasis is a chronic, inflammatory skin disorder in which the IL-23/Th17 axis plays an important role in inflammation. However, it is unclear whether modulation of NAD+ levels affects psoriasis, such as skin inflammation. Therefore, in this study, we investigated the effect of NAD+/NADH ratio modulation on imiquimod (IMQ)-induced, psoriasis-like skin inflammation in mice.Methods: Psoriasis-like skin inflammation was generated by daily topical application of IMQ cream. The severity of dermatitis was assessed using the Psoriasis Area Severity Index (PASI) and histochemistry. Expression of inflammatory cytokines was detected by enzyme-linked immunosorbent assay and quantitative PCR. Acetylation of NF-κB p65 and STAT3 was determined by Western blotting.Results: Dunnione improved IMQ-induced epidermal hyperplasia and inflammation, consistent with decreased levels of inflammatory cytokines (IL-17, IL-22, and IL-23) in skin lesions. Moreover, we found that an increase in the NAD+/NADH ratio by dunnione restored SIRT1 activity, thereby reduced imiquimod-induced STAT3 acetylation, which modulates the expression of psoriasis-promoting inflammatory cytokines, such as IL-17, IL-22, and IL-23.Conclusion: Pharmacological modulation of cellular NAD+ levels could be a promising therapeutic approach for psoriasis-like skin disease.Keywords: psoriasis, NQO1, NAD+, SIRT1, inflammatory cytokine